2018
DOI: 10.1261/rna.066910.118
|View full text |Cite
|
Sign up to set email alerts
|

DI-tector: defective interfering viral genomes’ detector for next-generation sequencing data

Abstract: Defective interfering (DI) genomes, or defective viral genomes (DVGs), are truncated viral genomes generated during replication of most viruses, including live viral vaccines. Among these, "panhandle" or copy-back (cb) and "hairpin" or snap-back (sb) DI genomes are generated during RNA virus replication. 5' cb/sb DI genomes are highly relevant for viral pathogenesis since they harbor immunostimulatory properties that increase virus recognition by the innate immune system of the host. We have developed , a user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 43 publications
3
56
0
Order By: Relevance
“…A re-analysis of rejected reads would identify these DVG hallmarks. With growing interest in this neglected part of the viral population, informatics tools such as ViReMa 48 , DI-tector 49 and VODKA 50 are emerging. These tools re-examine reads that potentially harbour jumbled or rearranged viral sequences and have enabled a broader appreciation of DVG diversity.…”
Section: Classes Types Structures and Diversitymentioning
confidence: 99%
“…A re-analysis of rejected reads would identify these DVG hallmarks. With growing interest in this neglected part of the viral population, informatics tools such as ViReMa 48 , DI-tector 49 and VODKA 50 are emerging. These tools re-examine reads that potentially harbour jumbled or rearranged viral sequences and have enabled a broader appreciation of DVG diversity.…”
Section: Classes Types Structures and Diversitymentioning
confidence: 99%
“…While this manuscript was in preparation, Beauclair et al, (2018)[36] reported development of an open-source bioinformatics DVG detection algorithm named DI-tector. DI-tector aligns the reads against a reference genome and examines non-perfectly aligned reads.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned, Beauclair et al ., [36] recently reported development of another open-source bioinformatics tool, named DI-tector, for identifying DVGs in HTS data. To demonstrate the ability of their tool to identify DVGs, the authors used publicly available HTS data from RNA extracted from Huh-7 cells infected with Sendai virus, another paramyxovirus (www.ncbi.nlm.nih.gov/sra, accession numbers SRX2600182 and SRX2600183).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations